Palladium-Catalyzed Denitrogenative Cross-Coupling of Silicon-Masked, Aryl-Substituted Diazenes and Aryl Bromides - Finck, Lucie; Dabrowski, Sarah; Oestreich, Martin (Synthesis, 2023)
A denitrogenative palladium-catalyzed C(sp2)–C(sp2) cross-coupling of aryl-substituted diazenes capped with a trimethylsilyl group and functionalized aryl bromides is reported. A PEPPSI™ catalyst in the presence of NaOt-Bu enables the activation of the N-aryl-N′-silyldiazene pronucleophile with concomitant loss of dinitrogen and subsequent coupling of the in-situ-formed aryl nucleophile. By this, biaryl compounds bearing a variety of substituents can be prepared.
Keywords: biaryls; chemoselectivity; cross-coupling; denitrogenation; diazene; palladium; silicon